2019
DOI: 10.3201/eid2505.180832
|View full text |Cite
|
Sign up to set email alerts
|

Human Monkeypox in Sierra Leone after 44-Year Absence of Reported Cases

Abstract: We note the reemergence of human monkeypox in Sierra Leone following a 44-year absence of reported disease. The persons affected were an 11-month-old boy and, several years later, a 35-year-old man. The reappearance of monkeypox in this country suggests a need for renewed vigilance and awareness of the disease and its manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 7 publications
2
50
0
1
Order By: Relevance
“…Monkeypox data from the DRC accounted for approximately one-third of the eligible articles [ 5 , 13 , 14 , 16 28 ]. The remaining articles had monkeypox data from the CAR [ 29 35 ], United States (US) [ 36 – 41 ], Nigeria [ 5 , 42 – 44 ], Republic of the Congo [ 15 , 45 47 ], Sierra Leone [ 42 , 48 , 49 ], Cameroon [ 5 , 50 ], Côte d’Ivoire [ 51 , 52 ], Gabon [ 53 , 54 ], United Kingdom (UK) [ 55 , 56 ], Israel [ 57 ], Liberia [ 42 ], Singapore [ 8 ], and South Sudan [formerly Sudan] [ 58 ]. (Note: two articles [ 5 , 42 ] described data for more than one country, therefore the total number of articles per country exceeds 48.)…”
Section: Resultsmentioning
confidence: 99%
“…Monkeypox data from the DRC accounted for approximately one-third of the eligible articles [ 5 , 13 , 14 , 16 28 ]. The remaining articles had monkeypox data from the CAR [ 29 35 ], United States (US) [ 36 – 41 ], Nigeria [ 5 , 42 – 44 ], Republic of the Congo [ 15 , 45 47 ], Sierra Leone [ 42 , 48 , 49 ], Cameroon [ 5 , 50 ], Côte d’Ivoire [ 51 , 52 ], Gabon [ 53 , 54 ], United Kingdom (UK) [ 55 , 56 ], Israel [ 57 ], Liberia [ 42 ], Singapore [ 8 ], and South Sudan [formerly Sudan] [ 58 ]. (Note: two articles [ 5 , 42 ] described data for more than one country, therefore the total number of articles per country exceeds 48.)…”
Section: Resultsmentioning
confidence: 99%
“…Animals (n = 16) were dosed with a three-dose (q48h) regimen of 20 (n = 8) or 5 (n = 8) mg/kg BCV via oral gavage, so that BCV pharmacokinetics could be determined following single and repeated doses. Blood (the maximum allowed per the IACUC protocol was ;0.5 ml) was collected at 8 time points (1,2,4,8,12,24,36, and 48 h) following the first BCV administration and at 9 time points (0, 1, 2, 4, 8, 12, 24, 36, and 48 h) following the last BCV administration via venipuncture (either the saphenous or jugular vein). To prevent dehydration and pain from the repeated blood collection, animals were given DietGel Criticare (ClearH 2 O; Portland, ME, USA) gel cup supplements, subcutaneous fluids (lactated ringers fluid), and meloxicam (4 mg/ml) every 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…While smallpox has been eradicated from the human population, recent studies have demonstrated a relatively easy path to virus reconstitution through the use of synthetic biology (1). Additionally, the number of monkeypox cases within Africa is growing, as is the number of African territories reporting the disease, possibly due in part to the waning immunity following smallpox vaccine cessation (2)(3)(4)(5)(6). MPXV has also been spread outside Africa, notably during the 2003 U.S. outbreak, as well as from recent imported cases of monkeypox in Israel, the United Kingdom, and Singapore (7)(8)(9).…”
mentioning
confidence: 99%
“…The outbreak in the US (2003) [40] and the outbreak in Nigeria (which started in 2017) [44] cover the largest part of the West African clade cases. This latter clade was also found in Sierra Leone [48,49] and the travel-related cases in Israel [57] and Singapore [8].…”
Section: Number Of Cases By Cladementioning
confidence: 63%
“…Monkeypox data from the DRC accounted for approximately one-third of the eligible articles [5,13,14,[16][17][18][19][20][21][22][23][24][25][26][27][28]. The remaining articles had monkeypox data from the CAR [29][30][31][32][33][34][35], United States (US) [36][37][38][39][40][41], Nigeria [5,[42][43][44], Republic of the Congo [15,[45][46][47], Sierra Leone [42,48,49],…”
Section: Number Of Reports By Countrymentioning
confidence: 99%